Analysis of immunologic comorbidities in ulcerative colitis patients: a tool to prevent exacerbations in ulcerative colitis cases - Rodríguez Meza, Miguel Ricardo (2022)
There have been previous studies, especially in Western countries and even in some areas in Asia, about extra-intestinal manifestations (EIMs) and its link with the outcome of inflammatory bowel disease (IBD), which includes Crohn’s disease (CD), and ulcerative colitis (UC). This link is crucial when discussing a patient’s prognosis and important when dealing with UC management. The aim of this study was to clarify the most common comorbidities associated with UC, emphasizing immunologic comorbidities in Japan. This study was a retrospective analysis performed at Nagoya University Hospital. The data collection started in March, 2019, and continued for two years. We retrieved the medical records of 105 patients with UC diagnosis, from which the data of 176 EIMs were extracted and analyzed. Results showed that EIMs with UC in the active phase accounted for 43.7% of total EIMs. Twenty-six patients with immune-mediated inflammatory disease frequently had an active phase (odds ratio [OR] 3.84, 99% CI, 1.44–10.27). Comorbidities showing an active manifestation of symptoms and UC in the active phase were significantly correlated in patients with immunological comorbidities, such as peripheral arthritis (r = 0.97, p < 0.01) and rheumatoid arthritis (RA) (r = 0.99, p < 0.01), as well as in patients with primary sclerosis cholangitis (PSC) (r = 0.98, p < 0.01). In conclusion, this analysis suggests the importance of having full comprehension of how immunological comorbidities affect the natural development of UC, which is of vital importance to prevent further UC complications and properly adjust the management of the disease.